Diffusing New Media as Know-How Digital Communication in Troubleshoot Maintenance of Pico Hydro Technology in Bengkulu, Indonesia - Naldo Naldo; Hardika Widi Satria; Dendy Adanta; warjito warjito (Jurnal Administrasi Bisnis Terapan, 2019)
Communication has an important role for spreading messages and ideas through various mediums. This research explains the important role of new media in community engagement activities and the dissemination of new information, innovations and technologies that have been done in 2017, especially for the graphic design via the internet on Pico Hydro's information technology in Batu Roto village, Bengkulu province, Indonesia. Community involvement itself is based on a special multidisciplinary perspective of communication and engineering. Pico Hydro is commonly used worldwide to generate electricity in rural areas, making it very useful for rural electrification. We conduct research to meet the needs of our plans in community engagement and use the theory of communication development to support the outcomes of this program. Communication development theory has a focus on dissemination of innovation. This research method is desk research of new media. This research argues that the application of Pico Hydro technology will have more impact on Batu Roto village community when combined with the method of social communication science development through digital media. The information contained in the infografic is expected to spread the idea to train the community in applying Pico Hydro technology for many homes in Batu Roto village so that it can solve the problem of electricity shortage in Bengkulu Province. Keywords: communication development; diffusion of innovations; infografic; pico hydro; psychology of colour; typographic; rural electrification; new media; digital communication